2018
DOI: 10.1111/acem.13383
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Novel Algorithm to Decrease Unnecessary Hospitalizations in Patients Presenting to a Community Emergency Department With Atrial Fibrillation

Abstract: Implementation of a novel algorithm to identify and treat low-risk patients with AFib can significantly decrease the rate of hospital admissions without increased ED returns. This simple algorithm could be adopted by other community hospitals and help lower costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Most published AF treatment protocols have been validated in high-volume tertiary care centers. De Meester et al demonstrated that the utilization of an AF treatment protocol could reduce admission rates even in a community-level hospital ED, based primarily on rate control rather than rhythm control [21]. Specifically, in this retrospective cohort study, there was a pre-implementation period from March 2013 to February 2014 with 586 patients included and a post-implementation period from March 2015 to February 2016 with 522 patients included.…”
Section: Strategies For Af Management In the Edmentioning
confidence: 82%
See 3 more Smart Citations
“…Most published AF treatment protocols have been validated in high-volume tertiary care centers. De Meester et al demonstrated that the utilization of an AF treatment protocol could reduce admission rates even in a community-level hospital ED, based primarily on rate control rather than rhythm control [21]. Specifically, in this retrospective cohort study, there was a pre-implementation period from March 2013 to February 2014 with 586 patients included and a post-implementation period from March 2015 to February 2016 with 522 patients included.…”
Section: Strategies For Af Management In the Edmentioning
confidence: 82%
“…Management of AF in the setting of the ED varies between countries and healthcare systems. Several trials of AF rhythm control strategies, including cardioversion, have demonstrated that AF in the ED can be treated safely and effectively, avoiding admission [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It is noteworthy that rate control rather than rhythm control is historically the preferred strategy in the United States, while in other Western countries such as Canada, Australia, and the United Kingdom, rhythm control is attempted in patients with AF who visit the ED [26,41,51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Real-time telemetry was the next evolution followed by implantable loop recorders and, most recently, smartphone technology. Improvements in technology have increased the utilization of mobile devices to deliver care at a distance; it has also shown to be an effective intervention to decrease anxiety and unnecessary hospitalizations and visits to EDs and UCs ( Demeester et al, 2018 ). Successful applications thereof to cardiac conditions in general—and AF in particular—have improved care, reduced symptomatology, and improved the quality of life.…”
Section: Introductionmentioning
confidence: 99%